직업에 대한 아동의 성별 고정관념의 인식 - 유미숙(Mi Sook Yoo) (Korean Journal of child studies, 1986)
The purpose of the present research was to study (1) children's sex-stereotyped perception toward adult occupations, and (2) the impact of traditional sex-stereotypes on future occupational preference. The subjects of this study were 120 children, 3 to 8 years of age enrolled in kindergatens and elementary schools. The instrument was developed by the researcher and consisted of 10 occupations which are traditionally sex-typed in Korean society. 5 male and female sex-typed occupations were selected with the participation of 200 college students. These occupations were illustrated on 10 pictorial cards, and short verbal explanations were given for each of them. It was found that: (1) Levels of children's perception of occupational sex stereotypes show that children aged five to six are marked comparatively higher than those aged three to four in the perception of occupation, children of seven to eight age indicate slightly downward; however, they are not differed significantly from those of five to six. (2) As far as levels of children'5 perception of occupational sex stereotypes aged three to four, five to six and seven to eight are concerned, interaction between age and sex was not shown significantly. Female children were more stereotyped at almost all age levels. (3) Irrespective of sex and age, all subjects were more familiar with male than with female occupations. (4) in the choice of future occupations, boys as well as girls preferred sex-stereotyped occupations for themselves. Boy's choices were more stereotyped than girls', but the number of kinds of occupations chosen by boys and by girls was not different. (5) There was an increase with age in the number of children who gave future occupational choices.